2018
DOI: 10.5194/jsss-7-443-2018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response and self-noise of the MET hydrophone

Abstract: An electrochemical hydrophone based on the principles of molecular electronic transfer (MET) has been described. The paper presents theoretical and experimental results for the sensitivity and the level of selfnoise determination for the MET hydrophone (METH) in the frequency range of 0.02-200 Hz, which determines the fields of acceptance of the devices being developed. An experimental model has been developed by using a force-balancing feedback. Different methods and techniques for its calibration have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Figure 5 shows the measurement results. Compared with the experimental results in [17,22], it can be seen that the measured self-noise in the presented frequency range was not inferior to that measured for a hydrophone with an air bubble. Similar tests with a hydrophone with a partially filled volume of liquid showed that the frequency response curve was more unstable with increasing pressure differences across the membranes.…”
Section: Self-noise Measurementmentioning
confidence: 43%
See 4 more Smart Citations
“…Figure 5 shows the measurement results. Compared with the experimental results in [17,22], it can be seen that the measured self-noise in the presented frequency range was not inferior to that measured for a hydrophone with an air bubble. Similar tests with a hydrophone with a partially filled volume of liquid showed that the frequency response curve was more unstable with increasing pressure differences across the membranes.…”
Section: Self-noise Measurementmentioning
confidence: 43%
“…The detailed scheme and principle of operation of the MET transducer element and hydrophone (METH) were described in the papers [3,17].…”
Section: Stabilization Methods Of the Frequency Response Of The Hydropmentioning
confidence: 99%
See 3 more Smart Citations